Sea Surface Reflection and Power Attenuation Analysis of Radio Wave in UHF Satellite Communications - Yuanming Ding; Jingjing Sun; Xue Wang (Institute of Advanced Engineering and Science, 2014)
Ultra High Frequency (UHF) band is increasingly widely used in military maritime satellite communications due to its good communication performance. Electromagnetic wave emitted by satellite is reflected when reaching the sea surface, and multipath fading is very serious which causes interference on the received signal, especially when satellite elevation angle is low. In this paper, the UHF band multipath effects of sea surface were studied following the general principles of modeling in multipath effects. The numerical simulation was made based on Rayleigh criterion and the judgment basis was obtained which determines whether the specula reflected component or diffuse reflected component dominates in the reflected wave, and then the reflection coefficient of sea surface in different polarization modes were calculated. Finally, the power attenuation of reflected wave relative to direct wave for different wind speeds were simulated and analyzed. Numerical simulation results show that the greater the wind speed is, the greater the power attenuation of reflected wave will become and the more serious multipath fading will be. In addition, diffuse reflection attenuation is more serious than specular reflection. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4787